Challenges faced by the Teachers and Students in online learning during COVID-19 - Muhammad Hafeez; Qaiser Abbas Kazmi; Fatima Tahira (Jurnal Cakrawala Pendidikan, 2022)
Most of the educational institutions (Universities, Schools and Colleges) in Pakistan are based on traditional method of learning and teaching. Although various institutions are now converting the learning methods from traditional to technology based online learning. At the end of 2019, the sudden outbreak of Pandemic disease Covid-19 has totally changed the learning and teaching system. Many educational institutions that were based on traditional methods of learning and teaching have to shift entirely on online learning and teachings. A survey based research has been conducted to highlight the challenges faced by students and teachers during Covid-19 in learning and teachings at undergraduate and graduate levels. The results of the research indicated that the students and teachers faced a lot of problems during the online learning and teaching. The online learning system of Pakistan, problems during online learning and solutions to the online learning problems are also discussed. This research will give a direction for the solution of problems associated with online learning and teachings.